2010
DOI: 10.1161/circinterventions.110.950097
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Neurological Events Associated With Carotid Artery Stenting in High-Surgical-Risk Patients

Abstract: Background-Comorbid and anatomic characteristics that portend higher procedural risk are well defined for carotid endarterectomy but less so for carotid artery stenting. Methods and Results-We pooled carotid stent data from 4 Cordis-sponsored trials (nϭ2104) with similar patient cohorts and end point determination to identify predictors of neurological death or stroke within 30 days of the procedure. Median age was 74 years (24% Ͼ80 years), 36% were women, and 24.2% were symptomatic in the previous 6 months. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 28 publications
0
16
1
1
Order By: Relevance
“…In a pooled analysis of 2,104 patients, the rate of 30-day stroke and/or death in asymptomatic and symptomatic patients was 3.8 and 5.3%, respectively [10]. The absence of this difference in our study can be explained by the paucity of asymptomatic patients.…”
Section: Discussioncontrasting
confidence: 51%
“…In a pooled analysis of 2,104 patients, the rate of 30-day stroke and/or death in asymptomatic and symptomatic patients was 3.8 and 5.3%, respectively [10]. The absence of this difference in our study can be explained by the paucity of asymptomatic patients.…”
Section: Discussioncontrasting
confidence: 51%
“…Cerebral hypoxia and ischaemia are important causes of death and disability, particularly during surgical procedures. Patients undergoing surgical procedures such as endarterectomies and cardiopulmonary bypass surgery have a much greater risk of stroke in the peri‐operative period due to thrombus formation and/or microemboli (Shaw et al 1985; Wolman et al 1999; Aronow et al 2010). Recent studies have found that short, non‐damaging ischaemic episodes before a longer ischaemic episode prevent the damage that would normally occur after the longer ischaemia (Gidday, 2006; Malhotra et al 2006; Roth et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…3 However, only 171 of 1989 patients received protamine in that study. Our study improves on these findings by comparing 555 patients treated with protamine to a control group of patients using propensity score adjustment.…”
Section: Discussionmentioning
confidence: 89%